Diversity of Culturable Bacterial Gut Microbiome of Oryctes rhinoceros Larvae and Their Potency as Source of Protease and Lipase Enzymes - Luqman Qurata Aini; Fibrianti Shinta Dewi; Irisa Trianti; Ito Fernando; Yogo Setiawan (AGRIVITA Journal of Agricultural Science, 2023)
Oryctes rhinoceros is an important pest of various coconut and palm species. Studies on the bacterial gut microbiome of O. rhinoceros larvae and their potential use as producers of industrial enzymes are still limited. This study aims to examine the diversity and abundance of culturable bacterial microbiome in the gut of O. rhinoceros and their potential to produce protease and lipase. This study consisted of several stages, i.e., collection of O. rhinoceros larvae from coconut plantations; isolation of culturable bacteria from larval gut; protease and lipase enzyme activity assays; and partial characterization of culturable gut bacteria in terms of morphology, physiology, and biochemistry. There were seven bacteria that were isolated from the gut of O. rhinoceros, which were differentiated by their morphotype. The seven bacterial isolates also showed variations in physiological, and biochemical characteristics, and the larval guts were dominated by Gram-positive bacteria. The Shannon diversity index was 1.33, evenness was 0.682, richness was 7, and the abundance of each type of bacteria varied between 2x105 and 9.1x1010. Bacteria UBOG1, UBOG3, and UBOG5 were able to produce protease, but all seven bacteria were unable to produce lipase. Thus, bacterial isolates UBOG1, UBOG3, and UBOG5 are potential to be used in industry.